2018
DOI: 10.5194/hess-22-2775-2018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MODIS and SWAT evapotranspiration over a complex terrain at different spatial scales

Abstract: Abstract. In most hydrological systems, evapotranspiration (ET) and precipitation are the largest components of the water balance, which are difficult to estimate, particularly over complex terrain. In recent decades, the advent of remotely sensed data based ET algorithms and distributed hydrological models has provided improved spatially upscaled ET estimates. However, information on the performance of these methods at various spatial scales is limited. This study compares the ET from the MODIS remotely sense… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 74 publications
(81 reference statements)
1
17
0
Order By: Relevance
“…7 revealed that the Revap has been a significant contributor to the TAE in the UBNRB for the last 40 years, with a mean annual contribution ranging from 21.4 % to 25.6 %; this could be due to the large coverage of deep-rooted Eucalyptus tree species that can access the saturated zone (Neitsch et al, 2011). The Revap component of this study appears consistent with the results of Abiodun et al (2018) and Benyon et al (2006), who reported the annual groundwater ET contribution to total ET ranged from 13 % to 72 % and 20 %, respectively, for south-eastern Australia and the Sixth Creek catchments. However, a detailed investigation of the contribution of Revap to the total actual evapotranspiration in the study area is required, which is beyond the scope of this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…7 revealed that the Revap has been a significant contributor to the TAE in the UBNRB for the last 40 years, with a mean annual contribution ranging from 21.4 % to 25.6 %; this could be due to the large coverage of deep-rooted Eucalyptus tree species that can access the saturated zone (Neitsch et al, 2011). The Revap component of this study appears consistent with the results of Abiodun et al (2018) and Benyon et al (2006), who reported the annual groundwater ET contribution to total ET ranged from 13 % to 72 % and 20 %, respectively, for south-eastern Australia and the Sixth Creek catchments. However, a detailed investigation of the contribution of Revap to the total actual evapotranspiration in the study area is required, which is beyond the scope of this study.…”
Section: Discussionsupporting
confidence: 91%
“…LULC change can modify the rainfall path to generate basin runoff by altering critical waterbalance components, such as groundwater recharge, infiltration, interception, and evaporation. McCartney et al (2012) and Alemseged and Tom (2015) described that the UBNRB experiences significant spatial and temporal climate variability. Less than 500 mm of precipitation falls annually near the Sudanese border, whereas more than 2000 mm falls annually in some areas of the southern basin (Awulachew et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the potential exists to provide a way to optimize streamflow performance using a multi-process approach, avoiding the problem of over-tuning based on peak annual flows. Given the proliferation of remote sensing products, the applications of these datasets has been already applied to the SWAT model for not only evapotranspiration (GLEAM, [5]; MODIS, [51][52][53]) but also for soil moisture (Soil Moisture Ocean Salinity, [54]; Soil Moisture Active Passive, [55]), and total terrestrial water (Gravity Recovery and Climate Experiment, [56]). The hydrologic community has the capability to derive independent estimates of parameters for most hydrological fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…The daily or even instantaneous estimation of ET c at the field scale is crucial for irrigation scheduling and is expected to have great application prospects in the future [240,259,262,263]. In this regard, the future direction of satellite-based ET estimates may focus on temporal downscaling either by extrapolation of instantaneous measurement [264], interpolation between two successive observations [201], data fusion of multiple satellites [25,260], and spatial downscaling using multiple satellites [265][266][267][268]. An example of early satellite-based remote sensing for ET is the MODIS Global Evapotranspiration Project (MOD16), which was established in 1999 to provide daily estimates of global terrestrial evapotranspiration using data acquired from a pair of NASA satellites in conjunction with Algorithm Theoretical Based Documents (ATBDs) [269].…”
Section: Evapotranspirationmentioning
confidence: 99%